Regulation of Foreign Currency Mortgage Loans : The Case of Transition Countries in Central and Eastern Europe - Dübel, Hans-Joachim; Walley, Simon (World Bank, Washington, DC, 2013)
The current financial crisis has had a major impact on the financial sectors of the Central and Eastern European (CEE) region. The impact has been exacerbated in many cases by the presence of foreign currency mortgage loans. The risk is both for the borrower, who has to make loan repayments in a currency different from that of the income he or she is generating, and for the banks, who need to fund themselves in a foreign currency. This study seeks to determine whether foreign currency mortgage loans really represent a major risk to all systems where they are present and then to assess what measures have been taken to deal with it. The optimal regulatory response will be appropriate for the macroeconomic context and also the consumer needs and best interests. A complete ban on the foreign currency product class appears appropriate for low-inflation economies, where consumer benefits from the product are low and the risk of speculation and has sent demand higher. Within that subset, fiscal support and other steps to further develop funding markets and improve affordability are likely to be required to help support local currency products. Also, these are the economies most likely to access the Euro in the near future, with limited exchange rate risk. Examples are Poland or the Czech Republic. For higher inflation economies facing choices of de-dollarization on one hand and possible imminent access to Eurozone on the other, foreign currency mortgages are likely to remain a part of the product menu for the near future. The challenge is to design a combined support and regulation strategy that creates a fair risk sharing arrangement between consumers and lenders and limits lender liquidity risks.